Analysis of the Effect of Fast Recovery Surgery Concept on Perioperative Nursing Care of Patients with Radical Resection of Cervical Cancer and Its Influence on Psychological Status. (9th August 2022) - Lu, Yun; Xu, Luxi; Lin, Xiaoyu; Qi, Xueling; Xia, Ling; Wang, Yuan
Abstract : Objective . To explore the applied effect of fast-track surgery concept in the perioperative nursing of patients undergoing radical cervical cancer surgery and its influence on mental state. Methods . The clinical data of 110 patients undergoing radical cervical cancer surgery in our hospital from May 2015 to May 2017 were retrospectively analyzed, and they were randomly divided into a research group ( n = 55) and a reference group ( n = 55). The reference group received routine clinical nursing, and the research group received fast-track surgical nursing. Then, we compared their nursing effect and influence on the mental state of patients in the two groups. Results . The Karnofsky performance status (KPS) scores of patients in the two groups after intervention were significantly lower than those before the intervention (P < 0.001), and after intervention, patients in the research group had significantly lower KPS scores as compared to patients in the reference group (P < 0.001). There was a significant decrease in the self-rating anxiety scale (SAS) scores and self-rating depression scale (SDS) scores of patients in the two groups after intervention in comparison with before intervention (P < 0.001), and patients in the research group after intervention had significantly lower SAS and SDS scores compared to the reference group (P < 0.001). Patients in the research group spent short time on expelling gas, eating, and getting out of bed as compared to the reference group (P < 0.001); after intervention, compared to patients in the reference group, patients in the research group had significantly higher scores in cognitive function, emotional function, social function, and physical function (P < 0.05). There was no significant difference in IgA, IgM, and IgG levels before intervention (P > 0.05). After intervention, the IgA, IgM, and IgG levels of patients in the two groups were all lower than before intervention, and patients in the research group had significantly higher IgA, IgM, and IgG levels as compared to the reference group (P < 0.001); the complication rate of patients in the research group was significantly lower than that in the reference group (P < 0.05). Conclusion . The fast-track surgery concept effectively helps improve the negative emotion of patients, shorten recovery time, improve quality of life, and reduce the impact on immune function in the radical cervical cancer surgery, and it is worthy of promotion and application, with a high safety.